Kenya National Hospital insurance fund reforms: implications and lessons for universal health coverage - Barasa, E; Rogo, K; Mwaura, N; Chuma, J (Taylor and Francis, 2018)
This article identifies and describes the reforms undertaken by the National Hospital Insurance Fund (NHIF) and examines their implications for Kenya's quest to achieve universal health coverage (UHC). We undertook a review of published and grey literature to identify key reforms that had been implemented by the NHIF since 2010. We examined the reforms undertaken by the NHIF using a health financing evaluation framework that considers the feasibility, equity, efficiency, and sustainability of health financing mechanisms. We found the following NHIF reforms: (1) the introduction of the Civil Servants Scheme (CSS), (2) the introduction of a stepwise quality improvement system, (3) the health insurance subsidy for the poor (HISP), (4) revision of monthly contribution rates and expansion of the benefit package, and (5) the upward revision of provider reimbursement rates. Though there are improvements in several areas, these reforms raise equity, efficiency, feasibility, and sustainability concerns. The article concludes that though NHIF reforms in Kenya are well intentioned and there has been improvement in several areas, design attributes could compromise the extent to which they achieve their intended goal of providing universal financing risk protection to the Kenyan population.